Indy Mutants: Live Long and Prosper - Frankel, Stewart; Rogina, Blanka (Frontiers in Genetics, 2012)
Indy encodes the fly homolog of a mammalian transporter of di and tricarboxylate components of the Krebs cycle. Reduced expression of fly Indy or two of the C. elegans Indy homologs leads to an increase in life span. Fly and worm tissues that play key roles in intermediary metabolism are also the places where Indy genes are expressed. One of the mouse homologs of Indy (mIndy) is mainly expressed in the liver. It has been hypothesized that decreased INDY activity creates a state similar to caloric restriction (CR). This hypothesis is supported by the physiological similarities between Indy mutant flies on high calorie food and control flies on CR, such as increased physical activity and decreases in weight, egg production, triglyceride levels, starvation resistance, and insulin signaling. In addition, Indy mutant flies undergo changes in mitochondrial biogenesis also observed in CR animals. Recent findings with mIndy knockout mice support and extend the findings from flies. mIndy−/− mice display an increase in hepatic mitochondrial biogenesis, lipid oxidation, and decreased hepatic lipogenesis. When mIndy−/− mice are fed high calorie food they are protected from adiposity and insulin resistance. These findings point to INDY as a potential drug target for the treatment of metabolic syndrome, type 2 diabetes, and obesity.